1998
DOI: 10.1037/0022-0663.90.3.435
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the differences in students' knowledge, interest, and strategic processing.

Abstract: The purpose for this research was threefold: to determine whether distinct and informative student profiles would emerge from knowledge, interest, and strategy measures specific to educational psychology; to compare these profiles with prior studies; and to explore changes in student profiles across an academic semester. As a result of cluster-analytic procedures, 3 distinct groups of participants emerged at pretest, and 4 emerged at posttest. One of the profiles that remained fairly consistent from pretest to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
1
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(125 citation statements)
references
References 60 publications
3
114
1
7
Order By: Relevance
“…Mitchell (1993) identified individual interest as an interest that people already have and bring to some context; for instance, some students will already have some interest in the course content before they take a course in the field. As with situational interest, individual interest has been found to have a positive influence on learning processes such as attention, recognition, and recall (Renninger & Wozniak, 1985) and academic motivation (Alexander & Murphy, 1998;Scheifele, 2001). …”
Section: Situational Interest and Individual Interestmentioning
confidence: 99%
See 3 more Smart Citations
“…Mitchell (1993) identified individual interest as an interest that people already have and bring to some context; for instance, some students will already have some interest in the course content before they take a course in the field. As with situational interest, individual interest has been found to have a positive influence on learning processes such as attention, recognition, and recall (Renninger & Wozniak, 1985) and academic motivation (Alexander & Murphy, 1998;Scheifele, 2001). …”
Section: Situational Interest and Individual Interestmentioning
confidence: 99%
“…There are a number of studies that show a positive impact of interest on learning (Alexander & Murphy, 1998;Scheifele, 1991;Scheifele, 2001;Schiefele, Krapp, & Winteler, 1992). Ainley, Hidi, and Berndorff (2002) examined the mediating processes of interest in reading comprehension and reported that topic interest influences reading comprehension as topic interest is associated with affective responses and is related to persistence with the text and learning.…”
Section: Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…Renninger (2006, 2011) have shown that interest is not fixed, but malleable, and often related to classroom learning: 'Teachers often think that students do or do not have interest, and might not recognize that they could make a significant contribution to the development of students' academic interest' (Hidi & Renninger, 2006, p. 111). Interest, too, can play a significant role in the level of learning that students are able to attain in given topic areas, largely because students' interests serve as contexts for learning (Alexander & Murphy, 1998;Renninger et al, 2002;Lipstein & Renninger, 2007).…”
Section: Theoretical Framework: Motivationmentioning
confidence: 99%